Penerapan Fuzzy Logic pada Sistem Pendeteksi Gas C4h10 dalam Ruangan sebagai Media untuk Menampilkan Bahaya Berbasis Android dan Graphical User Interface - Defnizal (Universitas Putra Indonesia YPTK Padang, 2019)
Gas is one of the needs that is widely used by the community. The use of gas is very much beneficial, for example, such as the use of gas in households and the use of gas in business or industry. However, there are things we must pay attention to when using gas in terms of safety. Because gas is volatile and there is a possibility of gas leakage which can cause a fire hazard. Therefore to reduce the impact of hazards that can be caused due to gas leakage, a gas leak detection device needs to be made using the MQ5 sensor and the status of the hazard level will be displayed through the android application. So that the existence of this tool will make it easier for users to know the level of gas levels and the level of danger of gas leaks. In this system there are 3 (three) levels of danger, namely safe, normal, and dangerous. If the gas level is high and in danger status, the system will provide information on the android application in the form of gas levels, danger levels and alarms. The use of Fuzzy methods in this system can be applied to explore knowledge and decision making, so that the Fuzzy method is applied to be expected to help in calculating the level of danger of gas leakage effectively and safely to use. In designing this system, the author uses the Fuzzy algorithm with the Mamdani method so that it can facilitate obtaining maximum results in determining the level of danger. From the resulting output can be information about the dangers of gas leakage.